Employee Engagement is the Key: Its Mediating Role between Person–Environment Fit and Organizational Commitment among Filipino Employees - Pacquing, Ma. Criselda T. (Makara Human Behavior Studies in Asia, 2023)
Employee engagement has been a popular topic in human resources management and development for several years now. However, the majority of the information on this construct came from the perspective of other cultures, and scientific research-based literature conducted on the engaging behavior of Filipinos, most notably on the antecedents and consequences, is limited. Thus, this study aimed to examine P–E fit and organizational commitment as an antecedent and the consequence of employee engagement, respectively. Similarly, the mediating function of employee engagement on the association of P–E fit with organizational commitment was explored. A total of 1252 employees from different Filipino-owned companies participated in the study through opportunity sampling. They answered three survey questionnaires that measure P–E fit, engagement, and organizational commitment. Results of the study revealed that P–E fit and organizational commitment are an antecedent and outcome of employee engagement, respectively. Findings further revealed that employee engagement mediates the connection between P–E fit and organizational commitment.